Упростите выражение:
1) (2m+3)(4m²-6m+9)
3) (m+2a)(m²-2am+4a²
5) (16y²+4yz²+z⁴)(4y-z²)
7) (4z⁶-2x³z³+x⁶)(2z³+x³)

2

Ответы и объяснения

2014-01-27T13:38:27+04:00
1. 2m³ + 3³
2. m³ + 2a³
3. 4e
³ - z5 (тут могу ошибаться)
4. 2z
⁶ - x⁶ (тут тоже)
2014-01-27T13:51:26+04:00
(2m+3)(4m²-6m+9)=  (2m+3)(2m-3)(2m-3)=(4m²-9)(2m-3)

(m+2a)(m²-2am+4a²)=  (m+2a)(m-2a)(m-2a)=(m-2a)(m²-4a²)

(16y²+4yz²+z⁴)(4y-z²) =  (4y-z²)(4y+z²)(4y+z²)=  (16y²-z⁴)(4y+z²) 

(4z⁶-2x³z³+x⁶)(2z³+x³)= (2z³-x³)(2z³-x³)(2z³+x³)=  (4z⁶-x⁶)(2z³-x³)